Studies of Axiological Space of Students Studying Pedagogics - Kokiel, Andrzej (Pedagogical Discourse, 2012)
The main contents tend to render, via analysis, an influence of social-economical elements on the evaluation system of Students of Pedagogy. Those people after graduation will probably start working with children, teenagers or people who are in a difficult life situation, so generally people who need a mature guide and a leader. It is proved that changes occurring in economy, politics and society, after Poland’s accession to the UE and Schengen area or regarding the world economical crisis, did not lead to any worrying changes in the evaluation system of the examined students. Moral and pro-social values stand high in their hierarchy. According to that, it can be found that those people are characterized by high moral qualifications which are fundamental in starting a career work as a pedagogue.